Selection of extra-early white quality protein maize (Zea mays L.) inbred lines for drought and low soil nitrogen resilient hybrid production - Annor, B.; Badu-Apraku, B. (Frontiers Media, 2024)
In West and Central Africa (WCA), drought and low soil nitrogen (low N) impede increased maize (Zea mays L.) productivity and production. Due to climate change, the two stresses usually occur together, leading to food, nutritional, and economic insecurity in the sub-region. There is, therefore, the need for the development and availability of high-yielding extra-early maturing white Quality Protein Maize (QPM) synthetics and hybrids with resilience to the prevailing stresses through the identification of superior climate smart (extra-early maturing) QPM inbreds under stress (drought and low soil N) conditions. The study was conducted to identify stress-resilient QPM inbred lines for hybrid production and assess the association between grain yield and other studied characters. During the 2012 minor and major rainy seasons, 96 extra-early white QPM inbreds and four (4) normal endosperm maize inbred checks were assessed inmulti-location trials under stress and optimal conditions in Nigeria. The experiments were laid out in a 10 × 10 simple lattice design with two replications. Data were recorded on grain yield and other agronomic traits. Significant variations (p < 0.01) were detected among the inbred lines for measured characters, indicating adequate genetic variability among the inbreds to allow for selection and improvement of grain yield and other measured traits. Grain yield was interrelated with all the traits used in the selection index. Moderate to high estimates of heritability were observed for most of the measured traits under stress conditions, indicating that the traits could be easily transmitted to the progenies. Fifty-seven out of the 96 QPM inbreds evaluated exhibited varying degrees of resilience to drought and low N. The QPM inbreds with desired traits may be used as genetic resources for the incorporation of tolerance genes into QPM populations in the tropics, as well as for the development of drought and low N resilient synthetics and hybrids in WCA.